The Role of Corporate Governance in Accelerating Financial Performance with Debt to Equity Ratio as a Moderating Variable - Ninava, Wiwin Aprelia (Equity: Jurnal Ekonomi, 2025)
This study aims to analyze the influence of corporate governance on profitability, with the debt to equity ratio acting as a moderating variable. The research focuses on 35 manufacturing companies over a period of five years. Purposive sampling was employed to select the total number of manufacturing companies for the study. Data analysis was assisted by SmartPLS 3 software. The results demonstrate that corporate governance has a positive effect on ROA. Firm age also significantly positively influences ROA. Similar outcomes are shown in the relationships between DER and ROA, Market to Book and ROA, and sales and ROA. However, DER does not moderate the relationship between corporate governance and ROA, Market to Book and ROA, or sales and ROA. The role of DER is proven to be a moderator in the relationship between firm age and ROA, and sales and ROA. This study confirms the importance of strong governance practices in enhancing company profitability. Companies should invest in strengthening their governance mechanisms, such as enhancing transparency, improving accountability systems, and ensuring board independence to increase ROA. DER does not always function effectively as a moderator in the impact of corporate governance on ROA. Financial managers should be cautious in using leverage as a tool to enhance profitability. Leverage should be strategically employed, considering other factors such as firm age and market conditions, to optimize its impact on ROA.